Internal curing by superabsorbent polymers in ultra-high performance concrete. (October 2015) - Justs, J.; Wyrzykowski, M.; Bajare, D.; Lura, P.
Abstract: To limit self-desiccation and autogenous shrinkage that may lead to early-age cracking of ultra-high performance concrete (UHPC), internal curing by means of superabsorbent polymers (SAP) may be employed. Cement pastes and UHPC with water-to-cement ratio below 0.25, with or without SAP, were studied. The absorption capacity of a solution-polymerized SAP was first determined on hardened cement pastes by SEM image analysis. It was observed that the SAP cavities become partially filled with portlandite during cement hydration. Isothermal calorimetry showed that water entrainment with SAP delays the main hydration peak, while after a couple of days it increases the degree of hydration in a manner similar to increasing the water-to-cement ratio. Internal curing by SAP is effective in reducing the internal relative humidity decrease and the autogenous shrinkage. Although the mechanical properties are affected by SAP addition, it is possible to reach compressive strengths of almost 150 MPa at 28 days. Highlights: SAP voids become partially filled with portlandite during hydration. Self-desiccation and autogenous shrinkage in UHPC can be efficiently reduced with internal curing by means of SAP. Compressive strength of UHPC with SAP can reach about 150 MPa at 28 days and above 170 MPa at 1 year. Hydration does not stop due to lack of free capillary spaces but may continue due to additional SAP porosity.